Traveling to Mars - Russell, Mark, 1971- (Ablaze, 2024)
From Eisner Award winning writer Mark Russell and artist Roberto Meli comes a compelling new sci-fi series... Traveling to Mars tells the story of former pet store manager Roy Livingston, the first human to ever set foot on Mars. Roy was chosen for this unlikely mission for one simple reason: he is terminally ill and therefore has no expectation of returning. Roy is joined on his mission to Mars by Leopold and Albert, two Mars rovers equipped with artificial intelligence, who look upon the dying pet store manager as a sort of god. Against the backdrop of not only his waning days but those of human civilization as well, Roy has ample time to think about where things went wrong for both of them and what it means to be a dying god. A riveting story of planetary exploration and of finding meaning in your final days. Collects the critically acclaimed 11-issue series plus cover gallery and bonus material.